Quality Of Life In Malaysian Small Town: Antecedent of The Major Determinants - Hussin, Nor Syahira; Muhamad Nazor, Nur' Aqilah; Mohamad, Zuraida; Mansor, Norudin (International Journal of Advanced Science Computing and Engineering, 2019)
Â This paper attempts to discuss the findings based on the survey on the relationship between determinants that reflected their influence on the quality of life among the residents living in a small town nearby one of the largest oil based manufacturing industries in Malaysia. Samples of the study were represented among those residents from the teenagers up to the old population categories. For ensuring an appropriate representation and adequate generalization, 306 questionnaires were distributed in urban and rural area. While analyzing the relationship as well as its impact, the study also examined possibility of differences between several selected profiles with the quality of life. In order to get more generalization from the pool of respondents, the further study may do deeper analysis such as focus in sub group respondents, besides observing samples in a much larger group from other town or cities in Malaysia.